2017
DOI: 10.1038/s41598-017-15033-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of single-nucleotide polymorphism in a fully humanized CYP3A mouse by genome editing technology

Abstract: Cytochrome P450, family 3, subfamily A (CYP3A) enzymes metabolize approximately 50% of commercially available drugs. Recently, we developed fully humanized transchromosomic (Tc) CYP3A mice with the CYP3A cluster including CYP3A4, CYP3A5, CYP3A7, and CYP3A43. Our humanized CYP3A mice have the CYP3A5*3 (g.6986G) allele, resulting in the almost absence of CYP3A5 protein expression in the liver and intestine. To produce model mice for predicting CYP3A5′s contribution to pharmacokinetics, we performed a single-nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…To further investigate quetiapine metabolism pathways, we used quetiapine metabolism inhibitors. Ketoconazole is well known to be a CYP3A inhibitor, including CYP3A4 and CYP3A5, having high inhibitory potency and producing reversible inhibition through competitive and non-competitive mechanisms [31][32][33][34][35][36][37] . In this way, in vitro studies have shown that 10 µM ketoconazole inhibits specific activity of CYP3A4 on HepaRG cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate quetiapine metabolism pathways, we used quetiapine metabolism inhibitors. Ketoconazole is well known to be a CYP3A inhibitor, including CYP3A4 and CYP3A5, having high inhibitory potency and producing reversible inhibition through competitive and non-competitive mechanisms [31][32][33][34][35][36][37] . In this way, in vitro studies have shown that 10 µM ketoconazole inhibits specific activity of CYP3A4 on HepaRG cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, chromosomal aberrations should be fully evaluated. 37 A new technology such as gene modification without genomic cleavage (DNA modification without DSB such as Dead Cas9, deaminase, or DNA methylation/demethylation). To prevent chromosomal breaks, translocations, and large deletions associated with genome editing, genome-editing technologies without DSB have been developed [38][39][40] as a new approach to genome editing that enables the direct irreversible conversion of one target DNA base into another in a programmable manner, such as the conversion of C to T or A to G with a deaminase.…”
Section: Classification By Purpose Of Genome Editingmentioning
confidence: 99%
“…Because hCYP3A-MAC/ hPXR mice have a 6986A.G mutation in the CYP3A5*3 allele, the expression level of CYP3A5 protein is negligible. Recently, we generated CYP3A-MAC mice with CYP3A5*1 by genome editing technology (Abe et al, 2017). Because CYP3A5 could be induced by RIF (Burk et al, 2004), further studies for comparison of induction between CYP3A4 and CYP3A5 in vivo may be accomplished by generation of a mouse model containing CYP3A5*1 and hPXR.…”
Section: Groupmentioning
confidence: 99%